Validation of heavy metals in geothermal to support water management practices and mitigation strategies - G.M. Idroes; D.P. Rezeki; K. Khairi; K. Khairan; R. Idroes; E. Suhartono; R. Prasetio; S.A. Rahman; S. Suhendrayatna (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: This study aimed to evaluate and validate the concentrations of six heavy metals, specifically lead, cadmium, copper, chromium, zinc, and iron, found in geothermal water from the Mount Kembar Region in Gayo Lues Regency, Aceh Province. This study primarily sought to investigate the health risks that these heavy metals may present and to deliver vital information that would aid in the advancement of water management practices and mitigation strategies in the locality. Understanding the levels of these metals is essential for preventing long-term health effects on the local population and ensuring sustainable use of geothermal water resources.METHODS: Water samples were taken from five geothermal sites in the region and analyzed with flame atomic absorption spectroscopy, a highly effective technique for the detection of trace metals. The flame atomic absorption spectroscopy technique was validated for precision, linearity, and accuracy, achieving R-squared values greater than 0.99, confirming the reliability of the analytical results. This confirmed that the identified concentrations of metals were reliable and could serve to evaluate the possible health risks faced by residents and users of the water source.FINDINGS: The analysis revealed that copper, chromium, zinc, and iron concentrations were within the permissible limits for safe drinking water as established by national and international health guidelines. However, elevated concentrations of lead and cadmium were detected in multiple sampled locations, surpassing the recommended safety thresholds. This implies a substantial danger to the health of those who drink or are exposed to this water, as both lead and cadmium are associated with severe health complications, including damage to the nervous system and kidneys. The findings underscore the urgent need for targeted water treatment and continuous monitoring, providing critical data to support sustainable water management and mitigation strategies in geothermal regions.CONCLUSION: The findings of this study underscore the urgent need for water treatment initiatives and continuous monitoring of geothermal water sources in the Mount Kembar Region. Although the analysis showed that the majority of metals were within safe ranges, the notably high levels of lead and cadmium require urgent measures to minimize health risks. Preventive measures, such as water filtration and public health advisories, should be implemented to safeguard the local population from the potential long-term exposure to these toxic metals.